The neutrophil-to-lymphocyte ratio for acute allograft rejection and delayed graft function prediction in kidney transplant recipients: a meta-analysis - Ryuu Damara Parisudha; Tanaya Ghinorawa; Indrawarman Soero Hardjo (Clinical Transplantation and Research)
Background : The neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) have been the focus of several observational studies investigating their roles in acute allograft rejection (AR) and delayed graft function (DGF) among kidney transplant (KT) recipients. This meta-analysis evaluated the impact of the NLR and PLR on the incidence of AR and DGF in KT recipients. Methods : We searched PubMed, MEDLINE and Science Direct from their inception through October 2023. Random effects models were used. To investigate potential sources of heterogeneity, we performed subgroup and meta-regression analyses. The Comprehensive Meta-Analysis ver. 3 software package was used. Results : Seven studies (247 KT recipients with AR or DGF and 475 controls) were analyzed. Our pooled analysis showed a significantly higher NLR in KT recipients with AR (weighted mean difference [WMD], 2.292; 95% confidence interval [CI], 1.449–3.135; P<0.001) than in controls. The preoperative NLR was insignificantly higher in patients with DGF (WMD, 0.871; 95% CI, –0.103 to 1.846; P=0.08). The PLR was insignificantly higher in KT recipients with AR than in controls (WMD, 32.125; 95% CI, –19.978 to 84.228; P=0.227). The PLR was not significantly different between KT recipients with DGF and controls. Region, publication year, sample size, donor type, biopsy type, AR type and Newcastle-Ottawa Scale score did not affect the outcomes of the meta-analysis. Meta-regression showed that publication year and donor type might be sources of heterogeneity. Conclusions: This study revealed a significantly higher NLR in patients with AR. This suggests that NLR may be utilized as a noninvasive marker for AR in KT recipients.